Foreign Language Beliefs and Behaviors of English Speaking Communities’ - Sukma Nur Ardini (Universitas PGRI Semarang, 2019)
The aim of this paper is to report the observation findings of foreign language beliefs and behaviors among three communities of English speaking communities’ specific of their cultural identity. The study used descriptive qualitative design since the author wants to describe the phenomenon happened in this study. Three English speaking communities were taken as the data; first, Krismit whatsApp group conversation; second, a private whatsApp conversation between two non-native speakers; third, a classroom talk. Those data were taken from the author’s cellphone, then the chats were exported, transcribed and analyzed well through their beliefs and behaviors specific of their cultural identity. The findings of the present study indicate that the awareness of using English pattern in two communities needs to be more highlighted, while the other community revealed the cultural matter in the form of expressions. Therefore, teachers’ and educators’ big effort in decreasing this issue is crucially needed.